Avaliação comparativa de tratamentos térmicos e químicos na preparação de carvão ativado a partir de torta prensada de Raphanus sativus para remoção de azul de metileno - Tatiana Martins Barbosa (2015)
In this work, different adsorbents materials were obtained employing radish (Raphanus sativus L.) oilseed cake, a solid residue from biodiesel production. The adsorbents were evaluated in natura and after chemical modification in the form of activated carbon. The chemical modification was carried out by treating the radish cakes with NaOH, KOH, H2SO4 and H3PO4. The carbonization occurred in muffle furnace or in conventional microwave oven. The adsorbents were characterized by scanning electron microscopy, thermogravimetric analysis, fluorescence spectrometry Xray, and infrared spectroscopy (FTIR). From the characterization and performance analysis of the manufactured adsorbents, the best material was selected for studies of adsorption of methylene blue (potential poluting agent) from aqueous solutions in batch experiments. The effects of different factors such as adsorbent dosage, agitation time, particle size and initial adsorbate concentration were evaluated in the adsorption studies. After evaluation of the best adsorption conditions, studies were performed to determine which kinetic equation best fits the experimental data; the pseudo first-order and pseudo second-order models were tested. The maximum adsorption capacity value was obtained by the equilibrium study, in which the empirical data were fitted to Langmuir, Freundlich and Temkin isotherm models. Results indicated that the activated carbon showed high adsorption capacity of methylene blue in aqueous solution and the maximum capacity obtained was 51,63 mg.g-1; this value is high in comparison to other types of adsorbents cited in the literature. The kinetic and equilibrium models that provided the best fits to the experimental data were respectively pseudo second-order and Langmuir, indicating that adsorption is predominantly chemical and occurs homogeneously. The results obtained in this study indicate the feasibility of using these byproducts of biodiesel production for the manufacturing of adsorbents for dye removal, given that they are an abundant agricultural waste product, present low cost, were obtained by a simple process, and showed high adsorptive capacity, representing an excellent alternative for the removal of methylene blue from industrial effluents. Therefore, they can contribute to sustainable development of biodiesel production.